KOMUNIKASI ANTAR ETNIS DI TENGAH KEBERAGAMAN BUDAYA ( STUDI DI KELURAHAN JATI MEKAR KECAMATAN KENDARI KOTA KENDARI ) - Irvandy, Irvandy (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
Abstract This study aims to determine the pattern of inter-ethnic communication in the midst of cultural diversity in the village of Jati Mekar, and wanted to know the forms of inter-ethnic communication. Basic theory used is intercultural communication and the concept of inter-ethnic communication, including DeVito and Anugrah. Informants in this study as many as 12 people, which is comprised of (5 community leaders who are considered to represent their ethnic; 7 regular informant or a combination of all ethnicities like Muna, Tolaki, Bugis, Javanese, Makasar), selected by purposive sampling or selected intentionally by the research objectives. Data collection using interviews (interview), observation. The data is analyzed using qualitative descriptive technique. The results of this study lead to the conclusion that â€œcommunication between ethnic diversity in the middle of culture (study in village jatiÂ  mekar city of kendari)â€(1) the pattern of inter-ethnic communication that includes; language as a symbol, a cross-cultural experience, interpersonal communication, experience of inter-ethnic communication, (2) The form of inter-ethnic communication in the village of Jati Mekar besides characterized by a variety of things common in intercultural communication such as; persuasive communication, cultural adaptation in communication, was also supported by the situation "setting" or the environment in which they interact relatively diffuse. Keywords: DeVito, Anugrah , Patterns and Forms of Communication Inter-Ethnic